Respostas
respondido por:
1
(i) |x + 9| = x + 9, se x + 9 >= 0
(ii) |x + 9| = -(x + 9), se x + 9 < 0
vamos resolver primeiro pela condição (i)
|x + 9| = 3
x + 9 = 3
x = - 6
Pela condição (ii)
|x + 9| = 3
- (x + 9) = 3
x + 9 = - 3
x = -12
(ii) |x + 9| = -(x + 9), se x + 9 < 0
vamos resolver primeiro pela condição (i)
|x + 9| = 3
x + 9 = 3
x = - 6
Pela condição (ii)
|x + 9| = 3
- (x + 9) = 3
x + 9 = - 3
x = -12
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás